Findings to the flora of Russia and adjacent countries: New national and regional vascular plant records, 1; Botanica Pacifica; Vol. 8, no. 1 - Verkhozina A. V. Alla Vasiljevna; Bolous V. N. Viktor Nikolaevich; Chernysheva O. A. Olga Aleksandrovna; Ebel A. L. Aleksandr Leonovich; Frizen N. V. Nikolay Valterovich; Yuzhakova M. A. Maria Aleksandrovna (2019, 2019)
Title screen